(untitled) (Al-Qamar, 2021)
Ihsan (احسان) is an Arabic term meaning goodness or excellence, When the Prophet (PBUH) was asked about Ihsan he replied: “It is to worship Allah as though you see Him, and though you do not see Him, you know that He sees you.” Mysticism, which through belief and practice helps Muslims attain nearness to Allah by way of Ihsan with personal experience. While structures vary greatly between different Sufi orders, the basic components are that of the murshid, the spiritual guide, and the murid, a follower who pledges allegiance, Bayah, to the murshid. These spiritual guides derive their authority and legitimacy from a chain of successive tutelage and instruction, Silsilah, which through continuous generations may reach back to a prominent saint or mystic. The role of the murshid is to act as a facilitator to the murid, instructing them on how to experience the Ihsaan in worship. Muslim Sufis have played an important role in social as well as in spiritual wellbeing of the community. They established Sufi Khankahs for religious education and spiritual purification of their followers. The basic purpose of these Khankahs to inject in community: Fear of Allah, trust of Allah, strict abhorrence of sharia and discipline. Pakistani government has taken direct control some of these Khankahs by establishing the department of Ministry of Auqaf. In this article the impact of Auqaf will be analysis on selected Sufi Khankahs of central Punjab in social, economic and political aspect.